2018
DOI: 10.3390/nu10121827
|View full text |Cite
|
Sign up to set email alerts
|

Complementary Biomarker Assessment of Components Absorbed from Diet and Creatinine Excretion Rate Reflecting Muscle Mass in Dialysis Patients

Abstract: To prevent protein energy malnutrition (PEM) and accumulation of waste products, dialysis patients require diet adjustments. Dietary intake assessed by self-reported intakes often provides biased information and standard 24-h urinary excretion is inapplicable in dialysis patients. We aimed to assess dietary intake via a complementary, less biased biomarker method, and to compare this to dietary diaries. Additionally, we investigated the prospective association of creatinine excretion rate (CER) reflecting musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…The total dialysate volume was measured by calculating the weight difference of the tank before and after the hemodialysis session. At the end of the dialysis, homogenous samples were taken from the dialysate for analysis [24]. Blood was drawn directly from the dialysis line, at the start of hemodialysis and five minutes before the end of the dialysis session.…”
Section: Sample Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The total dialysate volume was measured by calculating the weight difference of the tank before and after the hemodialysis session. At the end of the dialysis, homogenous samples were taken from the dialysate for analysis [24]. Blood was drawn directly from the dialysis line, at the start of hemodialysis and five minutes before the end of the dialysis session.…”
Section: Sample Collectionmentioning
confidence: 99%
“…To determine the combined excretion rate of tryptophan, kynurenine and 5-HIAA, we combined the dialysate excretion rate with the urinary excretion rate, if available [24]. The combined excretion rate of tryptophan, kynurenine and 5-HIAA was calculated as follows:…”
Section: Laboratory Measurementsmentioning
confidence: 99%
“…Interestingly, we also found a strong association between urinary taurine excretion and creatinine excretion. It is well known that 24 h urinary excretion of creatinine is a reflection of muscle mass [68,69]. It has previously been suggested that taurine is a promising nutritional agent to counteract the effects and development and sarcopenia [70].…”
Section: Discussionmentioning
confidence: 99%
“…All participating patients gave written informed consent. The methods of the study design have been described previously [ 15 17 ]. In short, inclusion criteria were twice or thrice weekly hemodialysis with 3–5 h per treatment, a hemodialysis vintage of ≥ 2 months, and absence of clinical signs of infection.…”
Section: Methodsmentioning
confidence: 99%